Effect of ε-Polylysine-Grape Seed Extract-Chitosan Coating on Preserving the Quality of Refrigerated Marinated Duck - GAO Jingyao, JIANG Jinhui, SHI Liu, ZHOU Zhi, XIONG Guangquan, WANG Lan, WU Wenjin, CHEN Lang, ZHANG Peng, HUANG Yun (Shipin Kexue, 2025)
Refrigerated marinated duck has a short storage period. In order to solve this problem, we prepared and characterized a functional chitosan-based coating with added ε-polylysine (ε-PL) as a natural bacteriostatic agent and grape seed extract (GSE) as an antioxidant. We then explored its effect on preserving the quality of refrigerated marinated duck. The results showed that functional coatings (CS-GSE, CS-ε-PL-GSE(a) and CS-ε-PL-GSE(b)) had better antimicrobial activity, antioxidant activity and thermal stability than did pure CS coating. During the cold storage period, the functional coatings significantly reduced the total viable count (TVC), thiobarbituric acid (TBA) value, total volatile base nitrogen (TVB-N) content, pH, color difference (ΔE*), and shear force of marinated duck. Marinated duck treated with functional coating CS-ε-PL-GSE(b) was found to have the highest sensory score, showing the best preservation effect, and the storage period was extended from 3 to 7 days.